Hot-rolled steel sheet
By controlling the chemical composition and metal structure of the hot-rolled steel plate, the problem of insufficient forming and fatigue characteristics of the hot-rolled steel plate in the prior art is solved, and high strength, excellent ductility, shear processing and fatigue characteristics after pressing are achieved.
Patent Information
- Application Number
- CN202380063334.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to provide hot-rolled steel plates with high strength, excellent forming properties, ultimate fracture plate thickness reduction rate, ductility, shear processing properties and fatigue after press forming.
By controlling the chemical composition and metal structure of hot-rolled steel plates, it is ensured that the distribution of metal structures in the thickness direction of the plate meets specific standards, including the area ratios of residual austenite, ferrite, and pearlite, as well as entropy, deficit normalization and cluster shadow values analyzed by grayscale symbiosis matrix method.
The high strength, excellent ductility and shear processing properties of the hot-rolled steel sheet are achieved, and excellent fatigue characteristics are possessed after pressing and forming, and the occurrence of cracking in bending is suppressed.
Smart Images

Figure CN119816614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hot-rolled steel sheet. Specifically, it relates to a hot-rolled steel sheet that is formed into various shapes by press working or the like, and in particular, it relates to a hot-rolled steel sheet that has high strength and ultimate fracture thickness reduction rate, has excellent ductility and shear workability, and has excellent fatigue properties after press forming.
[0002] This application claims priority based on Japanese Patent Application No. 2022-142994 filed in Japan on September 8, 2022, and the contents are incorporated herein by reference. Background Art
[0003] In recent years, efforts have been made to reduce carbon dioxide emissions in many fields from the perspective of protecting the global environment. Automobile manufacturers are also actively developing technologies to reduce vehicle body weight for the purpose of reducing fuel consumption. However, in order to ensure the safety of passengers, emphasis is also placed on improving collision resistance, so reducing vehicle body weight is not easy.
[0004] In order to take into account both lightweight vehicle bodies and collision resistance, the use of high-strength steel plates to thin the walls of components has been studied. Therefore, there is a strong desire for steel plates that have both high strength and excellent formability, and several technologies have been proposed in the past to meet these requirements. Since there are various processing styles for automotive components, the required formability varies depending on the components to be applied. Among them, the ultimate fracture thickness reduction rate and ductility are determined as important indicators of formability. The so-called ultimate fracture thickness reduction rate refers to the value obtained by the minimum value of the plate thickness of the tensile test piece before fracture and the plate thickness of the tensile test piece after fracture. When the ultimate fracture thickness reduction rate is low, it becomes easy to break at an early stage when the tensile strain in press forming is applied, so it is not preferred.
[0005] Automobile parts are formed by press forming, but the blank sheets for press forming are often manufactured by shearing, which has high productivity. The blank sheets manufactured by shearing need to have excellent end surface accuracy after shearing.
[0006] For example, if the shape of the end surface after shearing (sheared end surface) becomes a secondary sheared surface of sheared surface-fracture surface-sheared surface, the accuracy of the sheared end surface will be significantly deteriorated.
[0007] Furthermore, steel sheets used for automobile parts are required to have excellent fatigue properties after press forming.
[0008] For example, Patent Document 1 discloses a hot-rolled steel sheet which is a raw material for a cold-rolled steel sheet and has excellent surface properties after press working, wherein the Mn segregation and the P segregation in the center of the sheet thickness are controlled.
[0009] However, Patent Document 1 does not consider the limit fracture thickness reduction rate, shear workability, and fatigue properties after press forming of the hot-rolled steel sheet.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: International Publication No. 2020 / 044445
[0013] Non-patent literature
[0014] Non-patent document 1: J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) pp. 584-596
[0015] Non-patent document 2: DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546
[0016] Non-patent document 3: K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. P. S. Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the invention
[0017] Problems to be solved by the invention
[0018] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, excellent ductility and shear workability, and excellent fatigue properties after press forming.
[0019] Means for solving problems
[0020] The gist of the present invention is as follows.
[0021] (1) The chemical composition of the hot-rolled steel sheet according to one embodiment of the present invention contains, in terms of mass %, the following:
[0022] C: 0.050~0.250%,
[0023] Si: 0.05-3.00%,
[0024] Mn: 1.00~4.00%,
[0025] Sol.Al: 0.001~0.500%,
[0026] Cr: 0.060~2.000%,
[0027] P: 0.100% or less,
[0028] S: 0.0300% or less,
[0029] N: 0.1000% or less,
[0030] O: 0.0100% or less,
[0031] Ti: 0~0.500%,
[0032] Nb: 0~0.500%,
[0033] V: 0~0.500%、
[0034] Cu: 0-2.00%,
[0035] Mo: 0-1.00%,
[0036] Ni: 0-2.00%,
[0037] B: 0~0.0100%,
[0038] Ca: 0~0.0200%,
[0039] Mg: 0~0.0200%,
[0040] REM: 0~0.1000%、
[0041] Bi: 0~0.0200%,
[0042] As: 0~0.100%,
[0043] Zr: 0-1.00%,
[0044] Co: 0-1.00%,
[0045] Zn: 0-1.00%,
[0046] W: 0~1.00%, and
[0047] Sn: 0~0.05%,
[0048] The rest contains Fe and impurities.
[0049] Satisfying the following formulas (A) and (B),
[0050] The metal structure at a depth of 1 / 4 from the surface in the plate thickness direction is as follows in terms of area %:
[0051] Retained austenite is less than 3.0%,
[0052] Ferrite is 15.0% or more and less than 60.0%,
[0053] Pearlite is less than 5.0%,
[0054] The entropy value expressed by the following formula (1) obtained by analyzing the SEM image of the metal structure using the gray level co-occurrence matrix method is 10.7 or more.
[0055] The inverse difference normalized value represented by the following formula (2) is 1.020 or more.
[0056] The cluster shade value expressed by the following formula (3) is -8.0×10 5 ~8.0×10 5 ,
[0057] The standard deviation of the Mn concentration is 0.60 mass % or less,
[0058] The solid solution Cr concentration in the region starting from the surface and ending at a position 5 μm deep in the plate thickness direction, i.e., the outermost region, is 0.10 mass % or more.
[0059] The number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface is 1.0×10 4 Pieces / cm 2 the following.
[0060] 0.060%≤Ti+Nb+V≤0.500%(A)
[0061] Zr+Co+Zn+W≤1.00%(B)
[0062] In the above formulae (A) and (B), each element symbol represents the content of the element in mass %, and 0% is substituted when the element is not contained.
[0063] Wherein, P(i, j) in the following equations (1) to (5) is a gray level co-occurrence matrix, L in the following equation (2) is a normalization constant of the brightness value that can be obtained from the above SEM image, i and j in the following equations (2) and (3) are natural numbers from 1 to the above L, and μ in the following equation (3) is x and μ y They are represented by the following formulas (4) and (5), respectively.
[0064] Entropy = -Σ i Σ jP(i, j)log(P(i, j)) (1)
[0065]
[0066] Cluster shadow = Σ i Σ j (i+j-μ x -μ y ) 3 P(i,j) (3)
[0067] μ x =Σ i Σ j i(P(i,j)) (4)
[0068] μ y =Σ i Σ j j(P(i, j)) (5)(2) According to the hot-rolled steel sheet described in (1) above, the average crystal grain size in the surface region, i.e., the region starting from the surface and ending at a position at a depth of 20 μm in the thickness direction of the plate, may be less than 3.0 μm.
[0069] (3) The hot-rolled steel sheet according to (1) or (2), wherein the chemical composition may contain, in terms of mass %, one or more elements selected from the following:
[0070] Ti: 0.001~0.500%,
[0071] Nb: 0.001~0.500%,
[0072] V: 0.001~0.500%,
[0073] Cu: 0.01-2.00%,
[0074] Mo: 0.01~1.00%,
[0075] Ni: 0.02-2.00%,
[0076] B: 0.0001~0.0100%,
[0077] Ca: 0.0005~0.0200%,
[0078] Mg: 0.0005~0.0200%,
[0079] REM: 0.0005~0.1000%、
[0080] Bi: 0.0005~0.0200%,
[0081] As: 0.001~0.100%,
[0082] Zr: 0.01~1.00%,
[0083] Co: 0.01~1.00%,
[0084] Zn: 0.01~1.00%,
[0085] W: 0.01~1.00%, and
[0086] Sn: 0.01~0.05%.
[0087] Effects of the Invention
[0088] According to the above aspects of the present invention, it is possible to obtain a hot-rolled steel sheet having high strength and limit fracture thickness reduction rate, excellent ductility and shear workability, and excellent fatigue properties after press forming.
[0089] According to the above preferred aspects of the present invention, it is possible to obtain a hot-rolled steel sheet having the above-mentioned characteristics while suppressing the occurrence of bending cracking, that is, having excellent bending cracking resistance.
[0090] The hot-rolled steel sheet of the present invention is suitable as an industrial raw material used in automobile components, mechanical structural components, and even building components. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 This is an example of the sheared end surface of the hot-rolled steel sheet according to the example of the present invention.
[0092] Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet of a comparative example.
[0093] Figure 3 It is a figure for demonstrating the press forming performed in Example.
[0094] Figure 4 It is a figure for demonstrating the shape of the punch used for the said press forming. DETAILED DESCRIPTION
[0095] The chemical composition and metal structure of the hot-rolled steel sheet of this embodiment will be described in more detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications can be made within the scope of the present invention.
[0096] Regarding the numerical ranges described below with "to", the lower limit and the upper limit are included in the range. Regarding the numerical values expressed as "lower than" or "exceeding", the value is not included in the numerical range. In the following description, "%" about the chemical composition means "mass %" unless otherwise specified.
[0097] Chemical composition
[0098] The chemical composition of the hot-rolled steel sheet according to the present embodiment includes, by mass%, C: 0.050-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, sol.Al: 0.001-0.500%, Cr: 0.060-2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, and the remainder: Fe and impurities, satisfying formula (A) (0.060%≤Ti+Nb+V≤0.500%).
[0099] Each element is described in detail below.
[0100] C: 0.050~0.250%
[0101] C increases the area ratio of the hard phase and increases the strength of ferrite by combining with precipitation strengthening elements such as Ti, Nb, and V. When the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.055% or more, more preferably 0.060% or more, and further preferably 0.065% or more.
[0102] On the other hand, when the C content exceeds 0.250%, the area ratio of ferrite decreases, thereby reducing the ductility of the hot-rolled steel sheet. Therefore, the C content is set to 0.250% or less. The C content is preferably 0.150% or less.
[0103] Si: 0.05~3.00%
[0104] Si has the effect of promoting the formation of ferrite to improve the ductility of the hot-rolled steel sheet, and the effect of strengthening the ferrite by solid solution to increase the strength of the hot-rolled steel sheet. In addition, Si has the effect of making the steel sound by deoxidation (suppressing the generation of defects such as pores in the steel). When the Si content is less than 0.05%, the effect brought by the above-mentioned effects cannot be obtained. Therefore, the Si content is set to 0.05% or more. The Si content is preferably 0.40% or more, and more preferably 0.60% or more.
[0105] However, when the Si content exceeds 3.00%, the surface properties and chemical conversion treatment properties of the hot-rolled steel sheet, and further the ductility and weldability are significantly deteriorated, and the A3 transformation point is significantly increased. As a result, it becomes difficult to stably perform hot rolling. In addition, it becomes easy to generate ferrite excessively, and the strength is reduced. In addition, after cooling, austenite becomes easy to remain, and the limit fracture thickness reduction rate is reduced. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.50% or less, and more preferably 2.00% or less.
[0106] Mn: 1.00~4.00%
[0107] Mn has the effect of suppressing ferrite transformation to improve the strength of hot-rolled steel sheets. When the Mn content is less than 1.00%, the desired strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.10% or more, and more preferably 1.20% or more.
[0108] On the other hand, when the Mn content exceeds 4.00%, the morphology of the hard phase becomes periodic bands due to the segregation of Mn, and it becomes difficult to obtain the desired shear workability. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.50% or less, more preferably 3.00% or less, and further preferably 2.50% or less.
[0109] Ti: 0~0.500%
[0110] Nb: 0~0.500%
[0111] V: 0~0.500%
[0112] 0.060%≤Ti+Nb+V≤0.500%(A)
[0113] In the above formula (A), each element symbol represents the content of the element in mass %, and when the element is not contained, 0% is substituted.
[0114] Ti, Nb and V are elements that precipitate finely in steel as carbides and nitrides and improve the strength of steel through precipitation strengthening. If the total content of Ti, Nb and V is less than 0.060%, these effects cannot be obtained. Therefore, the total content of Ti, Nb and V is set to 0.060% or more. That is, the value of the middle side of the above formula (A) is set to 0.060% or more. It should be noted that it is not necessary to contain all of Ti, Nb and V, as long as any one of them is included, and the total content thereof is only required to be 0.060% or more. The total content of Ti, Nb and V is preferably 0.080% or more, and more preferably 0.100% or more. The contents of Ti, Nb and V are preferably 0.001% or more, respectively.
[0115] On the other hand, if the total content of Ti, Nb and V exceeds 0.500%, the workability of the hot-rolled steel sheet deteriorates. Therefore, the total content of Ti, Nb and V is set to 0.500% or less. That is, the value of the middle side of the above formula (A) is set to 0.500% or less. Preferably, it is 0.300% or less, more preferably 0.250% or less, and further preferably 0.200% or less.
[0116] Sol.Al: 0.001~0.500%
[0117] Al, like Si, has the function of deoxidizing steel and improving steel health, and has the function of promoting the formation of ferrite and improving the ductility of hot-rolled steel sheets. When the sol.Al content is less than 0.001%, the effects brought about by the above-mentioned functions cannot be obtained. Therefore, the sol.Al content is set to 0.001% or more. The sol.Al content is preferably 0.010% or more.
[0118] On the other hand, when the sol.Al content exceeds 0.500%, the above effect is saturated and it is not economically preferable, so the sol.Al content is set to 0.500% or less. The sol.Al content is preferably 0.450% or less, more preferably 0.400% or less, and further preferably 0.350% or less.
[0119] It should be noted that sol.Al refers to acid-soluble Al, and means solid-solution Al present in the steel in a solid-solution state.
[0120] Cr: 0.060~2.000%
[0121] Cr has the effect of improving the hardenability of hot-rolled steel sheets. In addition, Cr has the following effects: by combining with the desired manufacturing conditions, it is concentrated in the outermost region of the hot-rolled steel sheet to inhibit the growth of oxide scale and reduce the arithmetic mean roughness Ra after press forming. When the Cr content is less than 0.060%, the effect brought about by the above-mentioned effect cannot be obtained. Therefore, the Cr content is set to 0.060% or more. The Cr content is preferably 0.200% or more, more preferably 0.400% or more, and further preferably 0.600% or more.
[0122] On the other hand, when the Cr content exceeds 2.000%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.000% or less. The Cr content is preferably 1.800% or less, and more preferably 1.600% or less.
[0123] P: 0.100% or less
[0124] P is also an element that has the effect of improving the strength of the hot-rolled steel sheet by solid solution strengthening. Therefore, P may also be actively contained. However, P is an element that is easily segregated. If the P content exceeds 0.100%, the reduction in ductility and the limit fracture thickness reduction rate of the hot-rolled steel sheet caused by grain boundary segregation becomes significant. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.030% or less. The lower limit of the P content does not need to be specifically specified, and may also be 0%, but from the viewpoint of refining cost, it is preferably set to 0.001%.
[0125] S: 0.0300% or less
[0126] S forms sulfide inclusions in steel and reduces the ductility and ultimate fracture thickness reduction rate of the hot rolled steel sheet. If the S content exceeds 0.0300%, the ductility and ultimate fracture thickness reduction rate of the hot rolled steel sheet are significantly reduced. Therefore, the S content is set to 0.0300% or less. The S content is preferably 0.0050% or less. The lower limit of the S content does not need to be specifically specified and may be 0%, but from the viewpoint of refining cost, it is preferably set to 0.0001%.
[0127] N: 0.1000% or less
[0128] N has the effect of reducing the ductility and ultimate fracture thickness reduction rate of hot-rolled steel sheets. When the N content exceeds 0.1000%, the ductility and ultimate fracture thickness reduction rate of the hot-rolled steel sheet are significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably 0.0800% or less, more preferably 0.0700% or less, and further preferably 0.0100% or less. There is no need to specifically specify the lower limit of the N content, and it may also be 0%, but in the case of containing one or more of Ti, Nb and V to make the metal structure more refined, in order to promote the precipitation of carbonitrides, the N content is preferably set to 0.0010% or more, and more preferably 0.0020% or more.
[0129] O: 0.0100% or less
[0130] If a large amount of O is contained in the steel, coarse oxides that become fracture starting points are formed, causing brittle fracture and hydrogen cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, and more preferably 0.0050% or less. The O content may be 0%, but in order to disperse a large amount of fine oxides during deoxidation of the molten steel, the O content may be set to 0.0005% or more or 0.0010% or more.
[0131] The remainder of the chemical composition of the hot-rolled steel sheet of the present embodiment may also be Fe and impurities. In the present embodiment, the so-called impurities refer to substances mixed from ore, waste materials or manufacturing environment as raw materials, and / or substances allowed within the range that do not adversely affect the hot-rolled steel sheet of the present embodiment.
[0132] The hot-rolled steel sheet of the present embodiment may contain the following elements as optional elements in place of a portion of Fe. When these optional elements are not contained, the lower limit of the content is 0%. The optional elements will be described in detail below.
[0133] Cu: 0.01~2.00%
[0134] Mo: 0.01~1.00%
[0135] Ni: 0.02~2.00%
[0136] B: 0.0001~0.0100%
[0137] Cu, Mo, Ni and B all have the effect of improving the hardenability of the hot-rolled steel sheet. In addition, Cu and Mo have the effect of precipitating as carbides in steel to improve the strength of the hot-rolled steel sheet. Furthermore, Ni has the effect of effectively suppressing the grain boundary cracking of the slab caused by Cu when Cu is contained. Therefore, one or more of these elements may also be contained.
[0138] As mentioned above, Cu has the effect of improving the hardenability of hot-rolled steel sheets, and precipitates as carbides in steel at low temperatures to improve the strength of hot-rolled steel sheets. In order to more reliably obtain the effects brought about by the above-mentioned effects, the Cu content is preferably set to 0.01% or more, and more preferably set to 0.05% or more. However, when the Cu content exceeds 2.00%, grain boundary cracking of the slab may occur. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, and more preferably 1.00% or less.
[0139] As mentioned above, Mo has the effect of improving the hardenability of the hot-rolled steel sheet, and the effect of precipitating as carbide in the steel to improve the strength of the hot-rolled steel sheet. In order to more reliably obtain the effect brought about by the above-mentioned effect, it is preferred to set the Mo content to 0.01% or more, and more preferably to 0.02% or more. However, even if the Mo content is set to more than 1.00%, the effect brought about by the above-mentioned effect is saturated, which is not economically preferred. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, and more preferably 0.20% or less.
[0140] As mentioned above, Ni has the effect of improving the hardenability of hot-rolled steel sheets. In addition, Ni has the effect of effectively suppressing the grain boundary cracking of the slab caused by Cu when containing Cu. In order to more reliably obtain the effect brought about by the above-mentioned effect, the Ni content is preferably set to 0.02% or more. Since Ni is an expensive element, it is not economically preferable to contain a large amount of Ni. Therefore, the Ni content is set to 2.00% or less.
[0141] As mentioned above, B has the effect of improving the hardenability of the hot-rolled steel sheet. In order to more reliably obtain the effect brought about by this effect, it is preferred to set the B content to 0.0001% or more, and more preferably to 0.0002% or more. However, when the B content exceeds 0.0100%, the formability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. The B content is preferably set to 0.0050% or less.
[0142] Ca: 0.0005~0.0200%
[0143] Mg: 0.0005~0.0200%
[0144] REM: 0.0005~0.1000%
[0145] Bi: 0.0005~0.0200%
[0146] Ca, Mg and REM all have the effect of improving the ductility of the hot-rolled steel sheet by adjusting the shape of the inclusions in the steel to a preferred shape. In addition, Bi has the effect of improving the ductility of the hot-rolled steel sheet by refining the solidification structure. Therefore, one or more of these elements may also be contained. In order to more reliably obtain the effects brought about by the above-mentioned effects, it is preferred to set the content of any one or more of Ca, Mg, REM and Bi to 0.0005% or more. However, if the Ca content or the Mg content exceeds 0.0200%, or if the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, which may reduce the ductility of the hot-rolled steel sheet. In addition, even if the Bi content is set to more than 0.0200%, the effect brought about by the above-mentioned effects is saturated, which is not economically preferred. Therefore, the Ca content and the Mg content are set to less than 0.0200%, the REM content is set to less than 0.1000%, and the Bi content is set to less than 0.0200%. The Bi content is preferably 0.0100% or less.
[0147] Here, REM refers to a total of 17 elements including Sc, Y and lanthanoid elements, and the above-mentioned REM content refers to the total content of these elements. In the case of lanthanoid elements, they are added in the form of mixed rare earth alloys in industry.
[0148] As: 0.001~0.100%
[0149] As contributes to improving the ductility of the hot-rolled steel sheet by lowering the austenite transformation temperature and refining the prior austenite grains. In order to reliably obtain this effect, the As content is preferably set to 0.001% or more.
[0150] On the other hand, even if a large amount of As is contained, the above-mentioned effect is saturated, so the As content is made 0.100% or less.
[0151] Zr: 0.01~1.00%
[0152] Co: 0.01~1.00%
[0153] Zn: 0.01~1.00%
[0154] W: 0.01~1.00%
[0155] Zr+Co+Zn+W≤1.00%(B)
[0156] Sn: 0.01~0.05%
[0157] In the above formula (B), each element symbol represents the content of the element in mass %, and when the element is not contained, 0% is substituted.
[0158] Regarding Zr, Co, Zn and W, the inventors of the present invention have confirmed that even if these elements are contained in a total of 1.00% or less, the effect of the hot-rolled steel sheet of the present embodiment is not impaired. Therefore, one or more of Zr, Co, Zn and W may be contained in a total of 1.00% or less. That is, the value on the left side of the above formula (B) may also be set to 1.00% or less. Zr, Co, Zn and W may not be contained, so the content of each may also be 0%. In order to improve the strength by solid solution strengthening of the steel plate, the content of Zr, Co, Zn and W may also be 0.01% or more respectively.
[0159] In addition, the inventors of the present invention have confirmed that even if a small amount of Sn is contained, the effect of the hot-rolled steel sheet of the present embodiment will not be impaired. However, if a large amount of Sn is contained, defects may occur during hot rolling, so the Sn content is set to 0.05% or less. Sn may not be contained, so the Sn content may also be 0%. In order to improve the corrosion resistance of the hot-rolled steel sheet, the Sn content may also be set to 0.01% or more.
[0160] The chemical composition of the hot-rolled steel sheet mentioned above can be measured by general analytical methods. For example, it can be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). It should be noted that sol.Al can be measured using the filtrate after the sample is heated and decomposed with acid and measured by ICP-AES. C and S can be measured using the combustion-infrared absorption method, N can be measured using the inert gas melting-thermal conductivity method, and O can be measured using the inert gas melting-non-dispersive infrared absorption method.
[0161] When the hot-rolled steel sheet has a plating layer on the surface, the chemical composition analysis may be performed after the plating layer is removed by mechanical grinding or the like as necessary.
[0162] Metal structure of hot rolled steel plate
[0163] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.
[0164] The metal structure of the hot-rolled steel sheet of the present embodiment at a depth of 1 / 4 from the surface in the plate thickness direction is as follows in terms of area %: retained austenite is less than 3.0%, ferrite is 15.0% or more and less than 60.0%, and pearlite is less than 5.0%. The entropy value represented by the following formula (1) obtained by analyzing the SEM image of the above metal structure using the gray level co-occurrence matrix method is 10.7 or more, the deficit normalized value represented by the following formula (2) is 1.020 or more, and the cluster shadow value represented by the following formula (3) is -8.0×10 5 ~8.0×10 5 The standard deviation of Mn concentration is 0.60 mass % or less, the solid solution Cr concentration in the region starting from the above surface and ending at a position with a depth of 5 μm in the plate thickness direction, i.e., the outermost region, is 0.10 mass % or more, and the number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more at the above surface is 1.0×10 4 Pieces / cm 2 the following.
[0165] Therefore, the hot-rolled steel sheet of the present embodiment has high strength and limit fracture thickness reduction rate, as well as excellent ductility and shear workability, and can obtain excellent fatigue properties after press forming.
[0166] It should be noted that in this embodiment, the structure fraction, entropy value, deficit normalization value, cluster shadow value and standard deviation of Mn concentration of the metal structure in the region at a depth of 1 / 4 from the surface in the plate thickness direction are specified. The reason is that the metal structure at this position represents the representative metal structure of the steel plate.
[0167] In addition, the "surface" referred to here, when the hot-rolled steel plate has a coating, refers to the interface between the coating and the steel plate, and the "position at a depth of 1 / 4 from the surface" refers to the position of the hot-rolled steel plate at a depth of 1 / 4 of the plate thickness in the plate thickness direction from the surface.
[0168] Area ratio of retained austenite: less than 3.0%
[0169] Retained austenite is a metal structure that exists in the form of a face-centered cubic lattice even at room temperature. Retained austenite has the effect of improving the ductility of hot-rolled steel sheets through phase transformation plasticity (TRIP). On the other hand, since retained austenite transforms into high-carbon martensite during shearing, it becomes the starting point of cracks during deformation and the reason for the reduction in the limit thickness reduction rate of the fracture plate. When the area ratio of retained austenite is more than 3.0%, the above-mentioned effect becomes obvious, and the limit thickness reduction rate of the hot-rolled steel sheet decreases. Therefore, the area ratio of retained austenite is set to less than 3.0%. The area ratio of retained austenite is preferably less than 1.5%, and more preferably less than 1.0%.
[0170] The less the retained austenite, the better. Therefore, the area ratio of retained austenite may be 0%.
[0171] The area ratio of retained austenite is measured by X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, magnetic measurement, etc. In the present embodiment, the area ratio of retained austenite is measured by X-ray diffraction.
[0172] In the measurement of the area ratio of retained austenite by X-ray diffraction in the present embodiment, first, in the cross section at a depth of 1 / 4 from the surface in the thickness direction of the hot-rolled steel plate, a sample is collected in such a way that the metal structure in the area of 1 mm or more at any position in the rolling direction and 1 mm or more centered in the direction orthogonal to the rolling direction and the thickness direction can be observed. Co-Kα rays are used for the above sample to obtain the integrated intensity of a total of 6 peaks of α(110), α(200), α(211), γ(111), γ(200), and γ(220). Next, the volume ratio of retained austenite is calculated using the intensity average method from the above integrated intensity. The obtained volume ratio of retained austenite is regarded as the area ratio of retained austenite.
[0173] Area ratio of ferrite: 15.0% or more and less than 60.0%
[0174] Ferrite is a structure formed when fcc transforms into bcc at a relatively high temperature. Ferrite has a high work hardening rate, so it has the effect of improving the strength-ductility balance of hot-rolled steel sheets. In order to obtain the above effect, the area ratio of ferrite is set to 15.0% or more. It is preferably 20.0% or more, more preferably 25.0% or more, and even more preferably 30.0% or more.
[0175] On the other hand, since ferrite has low strength, if the area ratio is excessive, the desired strength cannot be obtained. Therefore, the ferrite area ratio is set to be less than 60.0%, preferably 50.0% or less, and more preferably 45.0% or less.
[0176] Area ratio of pearlite: less than 5.0%
[0177] Pearlite is a lamellar metal structure in which cementite is precipitated in layers between ferrites, and is a soft metal structure compared to bainite and martensite. If the area ratio of pearlite is 5.0% or more, carbon is consumed by cementite contained in pearlite, and the strength of martensite and bainite as the remaining structures decreases, and the desired strength cannot be obtained. Therefore, the area ratio of pearlite is set to less than 5.0%. The area ratio of pearlite is preferably 3.0% or less.
[0178] In order to improve the stretch flangeability of the hot-rolled steel sheet, the area ratio of pearlite is preferably reduced as much as possible, and the area ratio of pearlite is more preferably 0%.
[0179] Note that the hot-rolled steel sheet of this embodiment includes, as residual structures other than retained austenite, ferrite and pearlite, hard structures including one or more of bainite, martensite and tempered martensite having a total area ratio exceeding 32.0% and not more than 85.0%.
[0180] The area ratio of ferrite and pearlite is determined by the following method. First, a sample is collected in the center of the direction orthogonal to the rolling direction and the plate thickness direction in such a way that the metal structure in the area at a depth position of 1 / 4 from the surface in the plate thickness direction can be observed in the plate thickness section parallel to the rolling direction. The sample is set to a size of about 10 mm that can be observed in the rolling direction. Next, the above-mentioned sample section is ground and finished into a mirror surface, and then ground for 8 minutes at room temperature using colloidal silica with a particle size of 0.25 μm that does not contain an alkaline solution to remove the strain introduced into the surface layer of the sample. For an area of 200 μm or more at any position in the rolling direction of the above-mentioned sample section and 200 μm or more centered at a depth position of 1 / 4 from the surface in the plate thickness direction, the crystal orientation information is obtained by measuring the electron backscatter diffraction method at a measurement interval of 0.1 μm in the rolling direction and the plate thickness direction. For the above measurement, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL) was used. At this time, the vacuum degree in the EBSD analysis device was set to 9.6×10 -5 Pa or less, the acceleration voltage was set to 15 kV, the irradiation current level was set to 13, and the irradiation level of the electron beam was set to 62. It should be noted that the number of observation fields was set to 5 fields.
[0181] Furthermore, a reflected electron image is taken in each of the same observation fields in which the above-mentioned crystal orientation information is obtained. It should be noted that in the shooting of this image, the acceleration voltage is set to 15 kV, the irradiation current level is set to 12-13, and the irradiation level of the electron beam is set to 62. The focal distance (WD: Working Distance) is set to 5 mm. The area ratios of ferrite and pearlite are identified by the reflected electron image and the above-mentioned crystal orientation information. First, in the reflected electron image, the grains in which cementite precipitates in lamellar form are determined. In the reflected electron image, cementite is observed with white contrast. The cementite in the pearlite has a lamellar morphology, and the white contrast grains in the lamellar morphology observed at intervals of less than 1.0 μm are regarded as pearlite grains. By calculating the area ratio of the grains, the area ratio of pearlite is obtained.
[0182] Then, for the crystal orientation information obtained, the "Grain Average Misorientation" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device was used for the crystal orientation information of the crystal grains other than the crystal grains determined as pearlite, and the area with a Grain Average Misorientation value of 1.0° or less was determined as ferrite. At this time, the Grain Tolerance Angle was set to 15°, and the area ratio of the area determined as ferrite was obtained by calculating the area ratio of the area determined as ferrite.
[0183] The area ratio of the remaining structure is obtained by subtracting the area ratios of retained austenite, ferrite, and pearlite from 100%.
[0184] In addition, in the present embodiment, the rolling direction of the hot-rolled steel sheet is determined by the following method.
[0185] First, a test piece is collected in such a way that a cross section parallel to the surface of the hot-rolled steel sheet can be observed. The cross section of the test piece collected in the plate pressing direction is finished by mirror polishing and then observed using an optical microscope. The observation surface is set to a surface parallel to the surface of the plate at any depth in the range of 1 / 4 to 1 / 2 in the plate thickness direction, and in this observation surface, the direction parallel to the extension direction of the grains is determined as the rolling direction.
[0186] Entropy value: 10.7 or more, deficit normalization value: 1.020 or more
[0187] In order to suppress the generation of secondary shear surfaces, it is important to form fracture surfaces after fully forming shear surfaces, and it is necessary to suppress the generation of cracks from the tool tip at an early stage during shearing. For this reason, it is important that the periodicity of the metal structure is low and the uniformity of the metal structure is high. In this embodiment, the generation of secondary shear surfaces is suppressed by controlling the entropy value (E value) representing the periodicity of the metal structure and the inverse normalized value (I value) representing the uniformity of the metal structure.
[0188] The E value represents the periodicity of the metal structure. When the brightness is arranged periodically due to the formation of a banded structure, that is, when the periodicity of the metal structure is high, the E value decreases. In the present embodiment, since it is necessary to make a metal structure with low periodicity, it is necessary to increase the E value. If the E value is lower than 10.7, it becomes easy to generate a secondary shear surface. With the periodically arranged structure as the starting point, cracks are generated from the tip of the shearing tool in the very early stage of the shearing process to form a fracture surface, and then a shear surface is formed again. Thus, it is estimated that it becomes easy to generate a secondary shear surface. Therefore, the E value is set to be greater than 10.7. Preferably, it is greater than 10.8, and more preferably, it is greater than 11.0. The higher the E value, the more preferred it is. There is no particular upper limit, but it can also be set to less than 13.0, less than 12.5, or less than 12.0.
[0189] The I value represents the uniformity of the metal structure, and the wider the area of the region with a certain brightness, the higher it rises. A high I value means that the uniformity of the metal structure is high. In the present embodiment, since it is necessary to make a metal structure with high uniformity, it is necessary to increase the I value. If the I value is lower than 1.020, due to the influence of the precipitates in the grains and the hardness distribution caused by the difference in element concentration, cracks are generated from the tip of the shearing tool in the very early stage of the shearing process to form a fracture surface, and then a shear surface is formed again. As a result, it is estimated that it becomes easy to produce a secondary shear surface. Therefore, the I value is set to be greater than 1.020. Preferably, it is greater than 1.025, and more preferably greater than 1.030. The higher the I value, the more preferred it is, and the upper limit is not particularly specified, but it can also be set to less than 1.200, less than 1.150, or less than 1.100.
[0190] Cluster shadow value: -8.0×10 5 ~8.0×10 5
[0191] The cluster shadow value (CS value) indicates the strain of the metal structure. The CS value is a positive value if there are many points with brightness exceeding the average value of the brightness in the image obtained by photographing the metal structure, and a negative value if there are many points with brightness below the average value.
[0192] In the secondary electron image of the electron microscope, the brightness increases at the part with large surface unevenness of the observation object, and decreases at the part with small surface unevenness. The surface unevenness of the observation object is greatly affected by the particle size and intensity distribution in the metal structure. Regarding the CS value in this embodiment, it increases if the strength unevenness of the metal structure is large or the organizational unit is small, and decreases if the strength unevenness is small or the organizational unit is large.
[0193] In this embodiment, it is important to keep the CS value within the desired range close to 0. If the CS value is lower than -8.0×10 5, the reduction rate of the ultimate fracture thickness of the hot-rolled steel sheet decreases. It is presumed that this is because there are large grains in the metal structure, and these grains are preferentially fractured during the ultimate deformation. Therefore, the CS value is set to -8.0×10 5 Above. Preferably -7.5×10 5 More preferably -7.0×10 5 above.
[0194] On the other hand, if the CS value exceeds 8.0×10 5 , the reduction rate of the ultimate fracture thickness of the hot-rolled steel sheet decreases. It is presumed that this is because the microscopic strength in the metal structure is highly uneven, and the strain in the ultimate deformation is concentrated locally, making it easy to fracture. Therefore, the CS value is set to 8.0×10 5 Below. Preferably 7.5×10 5 Below, more preferably 7.0×10 5 the following.
[0195] The E value, I value, and CS value can be obtained by the following method.
[0196] In this embodiment, the shooting area of the SEM image taken in order to calculate the E value, I value and CS value is set to be 160 μm × 160 μm in the center of the direction orthogonal to the rolling direction and the plate thickness direction in the cross section parallel to the rolling direction with the plate thickness direction as the center of the 1 / 4 depth position from the surface, and the number of observation fields is set to 5 fields. For the shooting of the SEM image, a SU-6600 Schottky electron gun made by Hitachi High-Technologies Corporation is used, the emitter is set to tungsten, and the acceleration voltage is set to 1.5 kV. Based on the above settings, the SEM image is output with a magnification of 1000 times and a grayscale scale of 256 gray levels.
[0197] Next, the obtained SEM image was cut into an area of 880×880 pixels (the actual size of the observation area was 160μm×160μm), and the image was subjected to a smoothing process with a block grid size of 8×8 and a contrast enhancement limit ratio of 2.0 as described in non-patent document 3. The smoothed SEM image was rotated counterclockwise at every 1 degree from 0 to 179 degrees except for 90 degrees, and a total of 179 images were obtained by making images at every 1 degree. Next, for each of these 179 images, the GLCM method described in non-patent document 1 was used to collect the frequency values of the brightness between adjacent pixels in the form of rows and columns.
[0198] For the 179 frequency value rows and columns collected by the above method, k is set to the rotation angle with the original image, expressed as p k(k=0...89, 91, ...179). For each image, the generated p k After summing up all k (k = 0 ... 89, 91 ... 179), a 256 × 256 matrix P normalized so that the sum of each component becomes 1 is calculated. Furthermore, the E value, I value, and CS value are calculated using the following formulas (1) to (5) described in Non-Patent Document 2. It should be noted that the average value obtained by measuring all the fields of view is calculated.
[0199] P(i, j) in the following equations (1) to (5) is a grayscale co-occurrence matrix, and the value of the i-th row and j-th column of the row and column P is recorded as P(i, j). It should be noted that since the calculation is performed using a 256×256 row and column P as described above, if you want to emphasize this point, the following equations (1) to (5) can be corrected to the following equations (1') to (5'). Here, L in the following equation (2) is the number of grayscale levels that can be obtained by the SEM image (grayscale quantization level; Quantization levels of grayscale). In this embodiment, since the SEM image is output with a grayscale of 256 grayscale levels as described above, L is 256. i and j in the following equations (2) and (3) are natural numbers from 1 to the above L, and μ in the following equation (3) is x and μ y They are represented by the following formulas (4) and (5), respectively.
[0200] In the following equations (1') to (5'), the value of the i-th row and j-th column of the row P is expressed as P ij .
[0201] Entropy = -Σ i Σ j P(i, j)log(P(i, j)) (1)
[0202]
[0203] Cluster shadow = Σ i Σ j (i+j-μ x -μ y ) 3 P(i,j) (3)
[0204] μ x =Σ i Σ j i(P(i,j)) (4)
[0205] μ y =∑ i ∑ j j(P(i,j)) (5)
[0206]
[0207]
[0208] Standard deviation of Mn concentration: 0.60 mass % or less
[0209] The standard deviation of the Mn concentration of the hot-rolled steel sheet of the present embodiment is 0.60 mass % or less. Thus, the hard phase can be evenly dispersed, and cracks can be prevented from being generated from the tip of the shearing tool at an extremely early stage of the shearing process. As a result, the generation of secondary shear surfaces can be suppressed. The standard deviation of the Mn concentration is preferably 0.50 mass % or less, and more preferably 0.47 mass % or less. The lower limit of the standard deviation of the Mn concentration is preferably smaller as the value is smaller from the viewpoint of suppressing excessive fins, but due to the constraints of the manufacturing process, the substantive lower limit is 0.10 mass %.
[0210] The standard deviation of Mn concentration can be obtained by the following method. First, at the center of the direction orthogonal to the rolling direction and the plate thickness direction, a sample is collected in such a way that an area at a depth position of 1 / 4 from the surface in the plate thickness direction can be observed in a cross section parallel to the rolling direction. Although the sample varies depending on the measuring device, it is set to a size of about 10 mm that can be observed in the rolling direction. Then, after the above-mentioned sample is mirror-polished, an electron probe microanalyzer (EPMA) is used to measure the standard deviation of the Mn concentration. The measurement conditions are to set the acceleration voltage to 15 kV, set the magnification to 5000 times, and measure the distribution image of the Mn concentration in the range of 20 μm in the rolling direction of the sample and 20 μm in the plate thickness direction centered at a depth position of 1 / 4 from the surface in the plate thickness direction. More specifically, the measurement interval is set to 0.1 μm, and the Mn concentration of more than 40,000 places is measured. Next, the standard deviation of the Mn concentration is obtained by calculating the standard deviation based on the Mn concentration obtained from all the measurement points.
[0211] Solid solution Cr concentration in the outermost layer: 0.10 mass % or more
[0212] The inventors of the present invention have recognized that when the concentration of dissolved Cr in the outermost region (the region from the surface to a depth of 5 μm in the thickness direction of the plate) is high, the degradation of fatigue properties of the hot-rolled steel sheet after press forming can be suppressed by reducing the number density of Cr oxides at the surface with an equivalent spherical radius of 0.1 μm or more. If the concentration of dissolved Cr in the outermost region is less than 0.10 mass%, the degradation of fatigue properties of the hot-rolled steel sheet after press forming cannot be suppressed. Therefore, the concentration of dissolved Cr in the outermost region is set to be greater than 0.10 mass%. The concentration of dissolved Cr in the outermost region is preferably greater than 0.20 mass%, and more preferably greater than 0.40 mass%.
[0213] The solid solution Cr concentration in the outermost surface region may be set to 5.00 mass % or less.
[0214] It should be noted that in this embodiment, the region from the surface to a depth of 5 μm in the thickness direction refers to a layered region having a depth in the thickness direction ranging from the surface of the hot-rolled steel sheet as a starting point to a position with a depth of 5 μm in the thickness direction as an end point. As described above, the "surface" here refers to the interface between the coating and the steel sheet when the hot-rolled steel sheet has a coating.
[0215] The concentration of dissolved Cr in the outermost layer can be analyzed by GD-MS (Glow Discharge-Mass Spectrometry) analysis, which is an analysis method that tracks the composition change from the surface to the depth of the hot-rolled steel sheet over the elapse of discharge time.
[0216] In this embodiment, a sample is collected from an arbitrary position of the hot-rolled steel sheet, and the average value of the Cr concentration in mass % in the region from the surface to a depth of 5 μm in the thickness direction (a region with the surface as the starting point and a position with a depth of 5 μm in the thickness direction as the end point) is obtained when the sample is subjected to GD-MS analysis in the thickness direction. This operation is performed at any three or more locations (preferably five or more locations), and the average value of the obtained values is calculated to obtain the solid solution Cr concentration in the outermost region.
[0217] When the hot-rolled steel sheet has a plating layer on the surface, the depth position where the Fe concentration becomes 90 mass % in GD-MS analysis is regarded as the interface between the plating layer and the hot-rolled steel sheet, that is, the surface of the hot-rolled steel sheet.
[0218] Number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface: 1.0×10 4 Pieces / cm 2 the following
[0219] If the number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface exceeds 1.0×10 4 Pieces / cm 2, then when the hot-rolled steel sheet is press-formed, the surface roughness becomes larger. This surface roughness deteriorates the fatigue properties of the pressed parts, so it is preferably smaller. The Cr oxides defined here are those with an equivalent spherical radius of 0.1 μm or more, which are relatively coarse. It is believed that the coarse Cr oxides hinder the sliding between the hot-rolled steel sheet and the die, which becomes the cause of the increase in surface roughness. Generally speaking, Cr oxides exist in addition to the lowest part of the oxide scale, and have high adhesion to the base metal. Therefore, it is difficult to reduce the number density of Cr oxides on the surface in Cr-containing steel. In the present embodiment, this problem is solved by controlling the temperature during descaling and the temperature / reduction rate of rough rolling. Therefore, the number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface is set to 1.0×10 4 Pieces / cm 2 The number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface is preferably 0.8×10 4 Pieces / cm 2 Below, more preferably 0.6×10 4 Pieces / cm 2 the following.
[0220] The number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface can also be set to 0.1×10 4 Pieces / cm 2 above.
[0221] The number density of Cr oxides on the surface was measured by the following method.
[0222] A sample is cut out from the hot-rolled steel plate in such a way that the surface in the thickness direction becomes the observation surface. After degreasing the observation surface at 60°C for 60 seconds using FC-E6403 manufactured by Nihon Parkerizing, it is immersed in acetone for ultrasonic cleaning for 90 seconds. After that, more than 10 fields of view are observed at a magnification of 3000 times. The composition of the precipitate can be determined by EDS (energy dispersive X-ray spectrometer). The number density of Cr oxides is obtained by counting the number of regions containing Cr and O with an equivalent spherical radius of more than 0.1 μm in each field of view and dividing it by the measured area. It should be noted that when the precipitate is subjected to EDS analysis, if Cr and O are detected at more than 20 atomic percent, the precipitate is regarded as a Cr oxide.
[0223] In addition, when the hot-rolled steel sheet has a plating layer on the surface, the above-mentioned measurement is performed after removing the plating layer by pickling with fuming nitric acid.
[0224] Average crystal grain size in the surface area: less than 3.0 μm
[0225] By making the grain size in the surface area (the area from the surface to 20 μm deep in the thickness direction of the plate) fine, the in-bend cracking of the hot-rolled steel sheet can be suppressed. The higher the strength of the hot-rolled steel sheet becomes, the easier it is to generate cracks from the inside of the bend during bending (hereinafter referred to as in-bend cracking). The mechanism of in-bend cracking is estimated as follows. During bending, compressive stress is generated on the inside of the bend. Initially, the processing progresses while the entire inside of the bend is uniformly deformed, but if the processing amount becomes larger, the deformation cannot be borne by uniform deformation alone, and the deformation progresses due to local concentration of strain (generation of shear deformation band). The shear deformation band further grows, so that cracks are generated and grow along the shear band from the inside surface of the bend. It is estimated that the reason why in-bend cracking becomes easier to generate with high strength is that: due to the reduction of work hardening ability brought about by high strength, uniform deformation becomes difficult to perform, and deformation becomes more likely to be uneven, thereby generating a shear deformation band in the early stage of processing (or under loose processing conditions).
[0226] It should be noted that in the present embodiment, the region from the surface to a depth of 20 μm in the plate thickness direction refers to a layered region having a depth in the plate thickness direction ranging from the surface of the hot-rolled steel plate as a starting point to a position at a depth of 20 μm in the plate thickness direction as an end point.
[0227] Through the research of the inventors of the present invention, it is known that bending cracking becomes significant in steel plates with a tensile strength of 980MPa or above. In addition, the inventors of the present invention found that the finer the crystal grain size in the surface area of the hot-rolled steel plate, the more the local strain concentration is suppressed, and it becomes more difficult to produce bending cracking. In order to obtain the above-mentioned effect, the average crystal grain size in the surface area of the hot-rolled steel plate is preferably set to less than 3.0μm. Therefore, in this embodiment, the average crystal grain size in the surface area can also be set to less than 3.0μm. The average crystal grain size in the surface area is more preferably less than 2.5μm. The lower limit of the average crystal grain size in the surface area is not particularly specified, but can also be set to 0.5μm.
[0228] The crystal grain size in the surface area is measured using the EBSP-OIM (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy) method. The EBSP-OIM method is performed using a device obtained by combining a scanning electron microscope with an EBSP analysis device and OIM Analysis (registered trademark) manufactured by AMETEK. The analyzable area of the EBSP-OIM method is an area that can be observed by SEM. Although it also varies depending on the resolution of the SEM, according to the EBSP-OIM method, the minimum resolution that can be analyzed is 20nm.
[0229] In the cross-section made along the direction parallel to the rolling direction and the thickness direction of the hot-rolled steel plate, in the surface area from the surface to a depth of 20 μm in the thickness direction of the plate, measurements are performed at a magnification of 1200 times in at least 5 fields of view, and the areas where the angle difference between adjacent measurement points is 5° or more are defined as crystal grain boundaries, and the area-average crystal grain size is calculated.
[0230] It should be noted that retained austenite is not a structure generated by phase transformation below 600°C and does not have the effect of dislocation accumulation, so retained austenite is not an object of analysis in this measurement method. In the EBSP-OIM method, retained austenite with a crystal structure of fcc can be excluded from the analysis object.
[0231] Tensile strength properties
[0232] The tensile strength characteristics (tensile strength, total elongation) of the mechanical properties of the hot-rolled steel sheet were evaluated in accordance with JIS Z 2241: 2011. The test piece was set to the No. 5 test piece of JIS Z 2241: 2011. The sampling position of the test piece was set to the 1 / 4 position from the end face in the direction perpendicular to the rolling direction and the plate thickness direction, and the plate width direction was set as the length direction of the test piece.
[0233] The tensile strength of the hot-rolled steel sheet of the present embodiment is 980 MPa or more. Preferably, it is 1000 MPa or more. If the tensile strength is lower than 980 MPa, the applicable parts are limited and the contribution to the lightweighting of the vehicle body is small. The upper limit does not need to be particularly limited, but from the viewpoint of suppressing die wear, it can also be set to 1780 MPa.
[0234] In addition, the total elongation of the hot-rolled steel sheet of the present embodiment is preferably set to 10.0% or more, and the product of the tensile strength and the total elongation (TS×El) is preferably set to 13000 MPa·% or more. The total elongation is more preferably set to 11.0% or more, and further preferably set to 13.0% or more. In addition, the product of the tensile strength and the total elongation is more preferably set to 14000 MPa·% or more, and further preferably set to 15000 MPa·% or more. By setting the total elongation to 10.0% or more and setting the product of the tensile strength and the total elongation to 13000 MPa·% or more, it can greatly contribute to the lightweighting of the vehicle body without limiting the applicable parts.
[0235] Plate thickness
[0236] The plate thickness of the hot-rolled steel plate of the present embodiment is not particularly limited, but can also be set to 0.5 to 8.0 mm. When the plate thickness of the hot-rolled steel plate is less than 0.5 mm, it may be difficult to ensure the rolling completion temperature, and the rolling load becomes too large, making hot rolling difficult. Therefore, the plate thickness of the hot-rolled steel plate of the present embodiment can also be set to more than 0.5 mm. Preferably, it is more than 1.2 mm or more than 1.4 mm. On the other hand, when the plate thickness exceeds 8.0 mm, it is possible that the refinement of the metal structure becomes difficult, and it becomes difficult to obtain the above-mentioned metal structure. Therefore, the plate thickness can also be set to less than 8.0 mm. Preferably, it is less than 6.0 mm.
[0237] Plating
[0238] The hot rolled steel sheet of the present embodiment with the above-mentioned chemical composition and metal structure can also be made into surface treated steel sheet with the purpose of improving corrosion resistance etc. by making the surface equipped with coating. The coating can be an electroplated layer or a hot dip coating. As the electroplated layer, electrogalvanized layer, electroplated Zn-Ni alloy layer etc. can be exemplified. As the hot dip coating, hot dip galvanized layer, alloyed hot dip galvanized layer, hot dip aluminum layer, hot dip Zn-Al alloy layer, hot dip Zn-Al-Mg alloy layer, hot dip Zn-Al-Mg-Si alloy layer etc. can be exemplified. The coating adhesion amount is not particularly limited and can be set to be the same as before. In addition, by implementing appropriate chemical conversion treatment (such as coating and drying of chromium-free chemical conversion treatment liquid of silicate system) after plating, corrosion resistance can also be further improved.
[0239] Manufacturing conditions
[0240] A preferred method for producing the hot-rolled steel sheet of the present embodiment having the above-mentioned chemical composition and metal structure is as follows.
[0241] In the preferred method for manufacturing the hot-rolled steel sheet of the present embodiment, the following steps (1) to (11) are performed in sequence. It should be noted that the temperature of the slab and the temperature of the steel sheet in the present embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet. In addition, stress refers to the tension applied along the rolling direction of the steel sheet.
[0242] (1) After the slab is held in a temperature range of 700 to 850° C. for 900 seconds or more, it is further heated and held in a temperature range of 1100° C. or more for 6000 seconds or more.
[0243] (2) Descaling is performed once or more in a temperature range of 1150°C or more before rough rolling, and descaling is performed twice or more in a temperature range of 1130°C or more during rough rolling, and the maximum value of the total reduction ratio between each descaling in the temperature range of 1130°C or more is set to less than 40%.
[0244] (3) Hot rolling is performed in a temperature range of 850 to 1100° C. so that the total reduction ratio becomes 90% or more.
[0245] (4) A stress of 170 kPa or more is applied to the steel sheet from the end of the first stage of hot rolling to the start of the final stage of rolling.
[0246] (5) The rolling reduction in the final stage of hot rolling is set to 8% or more, and the hot rolling is completed so that the rolling completion temperature Tf becomes 900°C or more and lower than 1010°C.
[0247] (6) A stress of less than 200 kPa is applied to the steel sheet from the end of the hot rolling until the steel sheet is cooled to 800°C.
[0248] (7) After cooling to a temperature range of 600 to 780°C at an average cooling rate of 50°C / s or more after cooling to a temperature range of 50°C or less at a hot rolling completion temperature Tf-50°C or less within 1 second after hot rolling is completed. Among them, cooling to a temperature range of 600 to 780°C or less at an average cooling rate of 50°C / s or more after hot rolling is a more preferred cooling condition.
[0249] (8) In the temperature range of 600 to 780°C, slow cooling is performed for 2.0 seconds or more with an average cooling rate of less than 5°C / s.
[0250] (9) After the slow cooling is completed, cooling is performed so that the average cooling rate in the temperature range of 450 to 600° C. becomes 30° C. / s or more and less than 50° C. / s.
[0251] (10) Cooling is performed so that the average cooling rate in the temperature range from the coiling temperature to 450°C becomes 50°C / s or more.
[0252] (11) Coiling is performed in a temperature range of 350°C or lower.
[0253] By adopting the above-mentioned production method, it is possible to stably produce a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, excellent ductility and shear workability, and excellent fatigue characteristics after press forming.
[0254] (1) Slab temperature and holding time during hot rolling
[0255] The slabs used for hot rolling may be slabs obtained by continuous casting, slabs obtained by casting and blooming, etc. In addition, slabs obtained by hot working or cold working as needed may be used.
[0256] The slab for hot rolling is preferably kept in a temperature range of 700 to 850°C for more than 900 seconds when the slab is heated, and then further heated and kept in a temperature range of 1100°C or more for more than 6000 seconds. It should be noted that when the temperature is kept in the temperature range of 700 to 850°C, the temperature of the steel plate may be varied in the temperature range or may be set constant. In addition, when the temperature is kept at 1100°C or more, the temperature of the steel plate may be varied in the temperature range of 1100°C or more or may be set constant.
[0257] In the austenite transformation in the temperature range of 700-850°C, Mn is distributed between ferrite and austenite, and by extending the transformation time, Mn can diffuse in the ferrite region. As a result, the Mn microsegregation that is unevenly present in the slab can be eliminated, and the standard deviation of the Mn concentration can be significantly reduced. In addition, by maintaining the temperature range of 1100°C or more for more than 6000 seconds, the standard deviation of the Mn concentration can be significantly reduced.
[0258] Hot rolling is preferably performed using a reversible rolling mill or a tandem rolling mill as a multi-pass rolling. In particular, from the perspective of industrial productivity and the stress load on the steel plate during rolling, it is more preferred that at least the final two stages are set as hot rolling using a tandem rolling mill. Hot rolling includes rough rolling and finish rolling, and each is rolled multiple times (stages). Rough rolling is a process of rolling the slab to a minimum of 25 mm, and finish rolling is a process of rolling the rough-rolled plate to a target plate thickness.
[0259] (2) Descaling before rough rolling: once or more in the temperature range of 1150°C or more, Descaling during rough rolling: twice or more in the temperature range of 1130°C or more, Maximum total reduction ratio between descaling in the temperature range of 1130°C or more during rough rolling: less than 40%
[0260] By controlling the descaling conditions before rough rolling, the descaling conditions during rough rolling, and the rolling conditions between each descaling, the number density of Cr oxides on the surface of the hot-rolled steel sheet can be preferably controlled. Descaling can be performed by water jetting.
[0261] It is preferred to perform descaling at least once in a temperature range of 1150°C or higher before rough rolling. By performing descaling at least once in a temperature range of 1150°C or higher before rough rolling, the primary scale formed in the heating furnace can be removed, and the occurrence of subsequent descaling defects can be suppressed. As a result, the number density of Cr oxides on the surface of the hot-rolled steel sheet can be preferably controlled. The upper limit of the number of descaling in the temperature range of 1150°C or higher is not particularly limited, but can also be set to 5 times or less.
[0262] In the rough rolling, rolling and descaling are performed multiple times. In the rough rolling, descaling is performed between rolling and rolling or after multiple rolling. In the present embodiment, it is preferred that descaling is performed two or more times in a temperature range of 1130°C or higher in the rough rolling, and the maximum value of the total reduction ratio between each descaling in the temperature range of 1130°C or higher is set to less than 40%. By performing descaling two or more times in a temperature range of 1130°C or higher, the thickness of the scale formed in the front stage of the rough rolling is reduced, or the scale is removed, thereby preferably controlling the number density of Cr oxides on the surface of the hot-rolled steel sheet.
[0263] By setting the maximum value of the total reduction ratio between descaling steps in the temperature range above 1130°C to less than 40%, scale will not bite into the base metal during rolling between descaling steps, and the number density of Cr oxides on the surface of the hot-rolled steel sheet can be preferably controlled.
[0264] The total reduction ratio between each descaling in the temperature range of 1130° C. or higher can be expressed as {(t0-t1) / t0}×100(%), when the plate thickness before the nth descaling in the temperature range of 1130° C. or higher is set as t0, and the outlet plate thickness after the n+1th descaling in the temperature range of 1130° C. or higher is set as t1. Between the nth descaling and the n+1th descaling, rolling may be performed only once or multiple times.
[0265] (3) Hot rolling reduction ratio: 90% or more in the temperature range of 850 to 1100°C
[0266] By performing hot rolling in a temperature range of 850 to 1100°C with a total reduction ratio of 90% or more, the recrystallized austenite grains can be mainly refined, and the accumulation of strain energy in the non-recrystallized austenite grains can be promoted. In addition, the recrystallization of austenite can be promoted, and the atomic diffusion of Mn can be promoted, and the standard deviation of the Mn concentration can be reduced. Therefore, it is preferred to perform hot rolling in a temperature range of 850 to 1100°C with a total reduction ratio of 90% or more.
[0267] It should be noted that the hot rolling referred to here includes rough rolling and finish rolling.
[0268] It should be noted that the so-called total reduction rate in the temperature zone of 850 to 1100°C can be expressed as {(t0-t1) / t0}×100(%) when the entrance plate thickness before the initial rolling in the rolling in this temperature zone is set to t0 and the exit plate thickness after the final rolling in the rolling in this temperature zone is set to t1.
[0269] (4) Stress applied to the steel plate from the last stage of hot rolling to the start of the final stage of rolling: 170 kPa or more
[0270] It is preferred that a stress of 170 kPa or more be applied to the steel sheet from the last stage of hot rolling to the start of the last stage of rolling. This can reduce the {110} <001> The number of crystal orientations of the grains. {110} <001> Since it is a crystal orientation that is difficult to recrystallize, by suppressing the formation of this crystal orientation, recrystallization caused by the final stage of rolling can be effectively promoted. As a result, the banded structure of the hot-rolled steel sheet can be improved, the periodicity of the metal structure can be reduced, and the E value can be increased.
[0271] It should be noted that the final rolling of hot rolling here refers to the final rolling of finish rolling. For example, when finish rolling is performed in 7 passes of F1, F2, ..., F6, and F7, it refers to the 6th pass (F6).
[0272] When the stress applied to the steel sheet is less than 170 kPa, the E value may not be set to a desired value. The stress applied to the steel sheet is more preferably 190 kPa or more.
[0273] The so-called stress applied to the steel plate refers to the tension applied along the length direction of the steel plate, which can be controlled by adjusting the roller rotation speed in tandem rolling, and can be calculated by dividing the load in the rolling direction measured by the rolling stand by the cross-sectional area of the steel plate passing through the plate.
[0274] (5) Reduction ratio in the final stage of hot rolling: 8% or more, hot rolling finishing temperature Tf: 900°C or more and less than 1010°C
[0275] Preferably, the reduction rate in the final stage of hot rolling is set to 8% or more, and the hot rolling finishing temperature Tf is set to 900°C or more. By setting the reduction rate in the final stage of hot rolling to 8% or more, the recrystallization caused by the reduction in the final stage can be promoted. As a result, the banded structure of the hot-rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value increases. By setting the hot rolling finishing temperature Tf to 900°C or more, the excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the generation of ferrite in the final structure (the metal structure of the hot-rolled steel sheet after manufacture) can be suppressed, and a high-strength hot-rolled steel sheet can be obtained. In addition, by setting Tf to less than 1010°C, the coarsening of the austenite grain size can be suppressed, the periodicity of the metal structure can be reduced, and the E value can be set to the desired value.
[0276] (6) Stress applied to the steel plate from the final stage of hot rolling to the point where the steel plate is cooled to 800°C: less than 200 kPa
[0277] It is preferred that a stress of less than 200 kPa is applied to the steel plate after the final stage of hot rolling and before the steel plate is cooled to 800°C. By applying a stress of less than 200 kPa to the steel plate, the recrystallization of austenite preferentially progresses in the rolling direction, and the periodic increase of the metal structure can be suppressed. As a result, the E value can be set to a desired value. The stress applied to the steel plate is more preferably 180 kPa or less.
[0278] (7) After cooling to a temperature range below the hot rolling completion temperature Tf-50°C within 1 second after hot rolling is completed, accelerated cooling is performed at an average cooling rate of 50°C / s or more to a temperature range of 600 to 780°C.
[0279] In order to suppress the growth of austenite grains refined by hot rolling, it is more preferable to cool by 50°C or more within 1 second after hot rolling is completed, that is, the cooling amount within 1 second after hot rolling is completed is 50°C or more. In order to cool to a temperature range below the hot rolling completion temperature Tf-50°C within 1 second after hot rolling is completed, cooling with a large average cooling rate immediately after hot rolling is completed, such as spraying cooling water on the surface of the steel plate. By cooling to a temperature range below Tf-50°C within 1 second after hot rolling is completed, the crystal grain size of the surface layer can be refined, and the bending internal cracking resistance of the hot-rolled steel plate can be improved.
[0280] In addition, by accelerating cooling to a temperature range below 780°C at an average cooling rate of 50°C / s or more after the above cooling, the formation of ferrite and pearlite with a small amount of precipitation strengthening can be suppressed. As a result, the strength of the hot-rolled steel sheet is improved. It should be noted that the so-called average cooling rate here refers to the following value: the temperature drop of the steel plate from the start of accelerated cooling (when the steel plate is introduced into the cooling equipment) to the completion of accelerated cooling (when the steel plate is exported from the cooling equipment) divided by the required time from the start of accelerated cooling to the completion of accelerated cooling.
[0281] The upper limit of the cooling rate is not particularly specified, but if the cooling rate is increased, the cooling equipment becomes large-scale and the equipment cost becomes high. Therefore, if the equipment cost is considered, it is preferably 300°C / s or less. In addition, the cooling stop temperature of the accelerated cooling is preferably set to 600°C or more for the slow cooling described later.
[0282] (8) In the temperature range of 600 to 780°C, slow cooling is performed for 2.0 seconds or more with an average cooling rate of less than 5°C / s.
[0283] By performing slow cooling in a temperature range of 600 to 780°C with an average cooling rate of less than 5°C / s for 2.0 seconds or more, precipitation-strengthened ferrite can be sufficiently precipitated. Thus, both the strength and ductility of the hot-rolled steel sheet can be achieved.
[0284] The average cooling rate here refers to a value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of the accelerated cooling to the slow cooling stop temperature by the time required from the stop of the accelerated cooling to the stop of the slow cooling.
[0285] The time for slow cooling is preferably 3.0 seconds or more. The upper limit of the time for slow cooling is determined by the equipment layout, but it can be set to less than 10.0 seconds. In addition, the lower limit of the average cooling rate of slow cooling is not specifically set, but heating without cooling will be accompanied by a large investment in equipment, so it can also be set to 0°C / s or more.
[0286] (9) After the slow cooling is completed, the cooling is performed so that the average cooling rate in the temperature range of 450 to 600°C becomes 30°C / s or more and less than 50°C / s.
[0287] Preferably, after the slow cooling is completed, cooling is performed so that the average cooling rate in the temperature range of 450 to 600°C becomes 30°C / s or more and less than 50°C / s. By setting the average cooling rate in the temperature range to 30°C / s or more and less than 50°C / s, the CS value can be set to a desired value. When the average cooling rate is 50°C / s or more, a flat lath-shaped structure with low brightness is easily generated, and the CS value becomes less than -8.0×10 5 When the average cooling rate is lower than 30°C / s, the concentration of carbon in the non-transformed part is promoted, the strength of the hard structure increases, and the strength difference with the soft structure increases, so the CS value exceeds 8.0×10 5 .
[0288] It should be noted that the average cooling rate here refers to the following value: the temperature drop of the steel plate from the cooling stop temperature of slow cooling with an average cooling rate of less than 5°C / s to the cooling stop temperature of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s is divided by the time required from the stop of slow cooling with an average cooling rate of less than 5°C / s to the stop of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s.
[0289] (10) Average cooling rate in the temperature range from coiling temperature to 450°C: 50°C / s or more
[0290] In order to suppress the area ratio of pearlite and retained austenite and obtain desired strength and formability, the average cooling rate in the temperature range from the coiling temperature to 450° C. is preferably set to 50° C. / s or more. This can make the parent phase structure hard.
[0291] It should be noted that the average cooling rate here refers to the following value: the temperature drop of the steel plate from the cooling stop temperature of cooling at an average cooling rate of 30°C / s or more and less than 50°C / s to the coiling temperature is divided by the time required from the stop of cooling at an average cooling rate of 30°C / s or more and less than 50°C / s to coiling.
[0292] (11) Coiling temperature: below 350°C
[0293] The coiling temperature is set to 350° C. or less. By setting the coiling temperature to 350° C. or less, the precipitation amount of iron carbides can be reduced, and the unevenness of the hardness distribution in the hard phase can be reduced. As a result, the I value can be increased, and the generation of secondary shear planes can be suppressed.
[0294] Example
[0295] Next, the effect of one scheme of the present invention is described more specifically through an embodiment, but the conditions in the embodiment are a conditional example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this conditional example. As long as it does not deviate from the main purpose of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.
[0296] Steels having the chemical compositions shown in Tables 1 and 2 were melted and continuously cast to produce slabs having a thickness of 240 to 300 mm. The obtained slabs were used to produce hot-rolled steel sheets shown in Tables 5A to 6B under the production conditions shown in Tables 3A to 4B.
[0297] The average cooling rate of the slow cooling was set to be lower than 5°C / s. In addition, since the coiling temperature described in Table 4A and Table 4B is 50°C as the lower limit of measurement, the actual coiling temperature in the example described as 50°C is 50°C or lower.
[0298] For the obtained hot-rolled steel sheet, the area ratio of the metal structure, E value, I value, CS value, standard deviation of Mn concentration, solid solution Cr concentration in the outermost layer region, number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more at the surface, average crystal grain size in the surface region, tensile strength TS and total elongation El were obtained by the above method. The obtained measurement results are shown in Tables 5A to 6B.
[0299] It should be noted that the remaining structure is one or two or more of bainite, martensite, and tempered martensite.
[0300] Evaluation method of characteristics of hot-rolled steel sheets
[0301] Tensile properties
[0302] When the tensile strength TS is 980 MPa or more, the total elongation El is 10.0% or more, and the tensile strength TS×total elongation El is 13000 MPa·% or more, the hot-rolled steel sheet is judged as qualified as having high strength and excellent ductility. If even any one of the above conditions is not satisfied, the hot-rolled steel sheet is judged as unqualified as not having high strength and excellent ductility.
[0303] Limit fracture thickness reduction rate
[0304] The ultimate fracture thickness reduction rate of the hot-rolled steel sheet was evaluated by a tensile test.
[0305] The tensile test was performed in the same manner as that used to evaluate the tensile properties. When the plate thickness before the tensile test was set to t1 and the minimum plate thickness at the center of the width direction (short side direction) of the tensile test piece after fracture was set to t2, the limit fracture plate thickness reduction rate was obtained by calculating the value of (t1-t2)×100 / t1. The tensile test was performed 5 times, and the limit fracture plate thickness reduction rate was obtained by calculating the average value of the three times except the maximum and minimum values of the limit fracture plate thickness reduction rate.
[0306] When the limit breaking thickness reduction rate is 60.0% or more, the hot rolled steel sheet is judged as having a high limit breaking thickness reduction rate and is qualified. On the other hand, when the limit breaking thickness reduction rate is less than 60.0%, the hot rolled steel sheet is judged as not having a high limit breaking thickness reduction rate and is unqualified.
[0307] Shear processability (secondary shear surface evaluation)
[0308] The shear workability of the hot-rolled steel sheet was evaluated by a punching test.
[0309] Three punched holes were made in each example with a hole diameter of 10 mm, a clearance of 10%, and a punching speed of 3 m / s. Next, the cross section of the punched hole at right angles to the rolling direction and the cross section parallel to the rolling direction were buried in resin, and the cross-sectional shape was photographed using a scanning electron microscope. In the obtained observation photograph, it can be observed that Figure 1 or Figure 2 The shear end face shown in FIG. Figure 1 is an example of the sheared end surface of the hot-rolled steel sheet of the present invention. Figure 2 is an example of the shear end surface of the hot-rolled steel plate of the comparative example. Figure 1 For example, it is the shear end surface of collapsed edge-shear surface-fracture surface-flying fin. Figure 2 In terms of the shear end surface, it is a shearing end surface of collapsed edge-shear surface-fracture surface-shear surface-fracture surface-wing. Here, the collapsed edge refers to the area of the R-shaped smooth surface, the shear surface refers to the area of the punching end surface separated by shear deformation, the fracture surface refers to the area of the punching end surface separated by cracks generated near the blade tip, and the wing refers to the surface with a protrusion extending from the lower surface of the hot-rolled steel plate.
[0310] In the obtained shear end faces, two faces perpendicular to the rolling direction and two faces parallel to the rolling direction, when, for example, Figure 2In the case of the shear plane-fracture plane-shear plane shown in , it is judged that the secondary shear plane is formed. The four planes of each punched hole, a total of 12 planes, are observed. If no plane has a secondary shear plane, it is judged as a hot-rolled steel sheet with excellent shear workability and is recorded as "no" in the table. On the other hand, if even one secondary shear plane is formed, it is judged as a hot-rolled steel sheet that does not have excellent shear workability and is unqualified, and is recorded as "yes" in the table.
[0311] Fatigue properties after press forming
[0312] The fatigue properties after press forming were evaluated by the arithmetic mean roughness Ra of the surface of the hot-rolled steel sheet after press forming.
[0313] For the other surface B of the test piece 10 in which one surface A in the plate thickness direction of the hot-rolled steel plate is ground and the plate thickness is set to be less than 1.6 mm, as shown in FIG. Figure 3 As shown in , the punch 1 is pressed with a load of 2.5 t while being pulled in one direction D to perform press forming. The punch shape is shown in Figure 4 (FIG. 9 of Japanese Patent No. 5655394) The hot-rolled steel sheet after press forming was corrected in shape by a leveler, and then the arithmetic mean roughness Ra of the surface was measured by the following method.
[0314] For the surface of a sample of 1000mm×1000mm, locations with an interval of 200mm in the rolling direction and in a direction perpendicular to the rolling direction and the plate thickness direction are used as measurement locations, and the surface roughness is measured at each measurement location. The measurement length at each measurement location is set to 5mm. The roughness curve is obtained by sequentially applying contour curve filters with cutoff values λc and λs to the cross-sectional curve obtained by the measurement. Specifically, the components with a wavelength λc of less than 0.8mm and the components with a wavelength λs of more than 2.5mm are removed from the obtained measurement results to obtain a roughness curve. Based on the obtained roughness curve, the arithmetic mean roughness Ra of each measurement location is calculated in accordance with JIS B 0601:2013. By calculating the average value of the obtained values, the arithmetic mean roughness Ra of the surface of the hot-rolled steel plate after press forming is obtained.
[0315] For the hot-rolled steel sheet after press forming, if the arithmetic mean roughness Ra of the surface is 3.0 μm or less, it is judged as a hot-rolled steel sheet having excellent fatigue properties after press forming. On the other hand, if the arithmetic mean roughness Ra of the surface exceeds 3.0 μm, it is judged as a hot-rolled steel sheet not having excellent fatigue properties after press forming.
[0316] Resistance to internal cracking during bending
[0317] The bending crack resistance was evaluated by the following bending test.
[0318] At a position 1 / 2 from the end face of the hot-rolled steel plate in the direction perpendicular to the rolling direction and the plate thickness direction, a 100 mm × 30 mm strip-shaped test piece was cut out to obtain a bending test piece. For both bending (L-axis bending) in which the bending ridgeline is parallel to the rolling direction (L direction) and bending (C-axis bending) in which the bending ridgeline is parallel to the direction (C direction) perpendicular to the rolling direction and the plate thickness direction, the test was conducted according to the V-block method of JIS Z 2248:2022 (bending angle θ is 90°). Thus, the minimum bending radius without cracking was obtained, and the resistance to internal cracking in bending was investigated. The value obtained by dividing the average value (R) of the minimum bending radius of the L axis and the C axis by the plate thickness (t) was set as the limit bending R / t, which was used as an index value of resistance to internal cracking in bending. When R / t is 2.5 or less, it is judged to be a hot-rolled steel plate with excellent resistance to internal cracking in bending.
[0319] Regarding the presence or absence of cracks, the cross section of the test piece after the test was cut parallel to the bending direction and perpendicular to the plate surface, mirror polished, and then cracks were observed under an optical microscope. When the length of the crack observed on the inner side of the bend of the test piece exceeded 30 μm, it was judged that cracks were present.
[0320] [Table 1]
[0321]
[0322] [Table 2]
[0323]
[0324] [Table 3A]
[0325]
[0326] [Table 3B]
[0327]
[0328] [Table 4A]
[0329]
[0330] [Table 4B]
[0331]
[0332] [Table 5A]
[0333]
[0334] [Table 5B]
[0335]
[0336] [Table 6A]
[0337]
[0338] [Table 6B]
[0339]
[0340] From Tables 5A to 6B, it can be seen that the hot-rolled steel sheets of the examples of the present invention have high strength and ultimate fracture thickness reduction rate, as well as excellent ductility and shear workability, and have excellent fatigue properties after press forming. In addition, it can be seen that the hot-rolled steel sheets of the examples of the present invention, in which the average crystal grain size of the surface layer region is less than 3.0 μm, have excellent resistance to bending internal cracking in addition to the above-mentioned properties.
[0341] On the other hand, it is found that the hot-rolled steel sheets of the comparative examples have deteriorated in one or more characteristics.
[0342] Industrial Applicability
[0343] According to the above-mentioned embodiment of the present invention, a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, excellent ductility and shear workability, and excellent fatigue properties after press forming can be provided. In addition, according to the above-mentioned preferred embodiment of the present invention, a hot-rolled steel sheet having the above-mentioned properties and suppressing the occurrence of bending cracking, i.e., excellent bending cracking resistance can be obtained.
[0344] The hot-rolled steel sheet of the present invention is suitable as an industrial raw material used in automobile components, mechanical structural components, and even building components.
Claims
1. A hot rolled steel plate, characterized in that: The chemical composition contains by mass %: C:0.050~0.250%、 Si: 0.05-3.00%, Mn: 1.00~4.00%, Sol.Al: 0.001~0.500%, Cr:0.060~2.000%、 P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0~0.500%, Nb: 0~0.500%, V:0~0.500%、 Cu: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B:0~0.0100%、 Ca: 0~0.0200%, Mg: 0~0.0200%, REM: 0~0.1000%、 Bi: 0~0.0200%, As: 0~0.100%, Zr:0~1.00%、 Co: 0-1.00%, Zn: 0-1.00%, W: 0~1.00%, and Sn: 0~0.05%, The rest contains Fe and impurities. Satisfying the following formulas (A) and (B), The metal structure at a depth of 1 / 4 from the surface in the plate thickness direction is as follows in terms of area %: Retained austenite is less than 3.0%, Ferrite is 15.0% or more and less than 60.0%, Pearlite is less than 5.0%, The entropy value expressed by the following formula (1) obtained by analyzing the SEM image of the metal structure using the gray level co-occurrence matrix method is 10.7 or more. The normalized deficit value represented by the following formula (2) is 1.020 or more. The cluster shadow value expressed by the following formula (3) is -8.0×10 5 ~8.0×10 5 , The standard deviation of the Mn concentration is 0.60 mass % or less, The solid solution Cr concentration in the region starting from the surface and ending at a position 5 μm deep in the plate thickness direction, i.e., the outermost region, is 0.10 mass % or more. The number density of Cr oxides with an equivalent spherical radius of 0.1 μm or more on the surface is 1.0×10 4 Pieces / cm 2 the following, 0.060%≤Ti+Nb+V≤0.500% (A) Zr+Co+Zn+W≤1.00% (B) The symbol of each element in the formula (A) and (B) represents the content of the element in mass %, and 0% is substituted when the element is not contained. Wherein, P(i, j) in the following equations (1) to (5) is a gray level co-occurrence matrix, L in the following equation (2) is the number of gray scale levels that can be obtained by the SEM image, i and j in the following equations (2) and (3) are natural numbers from 1 to L, and μ in the following equation (3) is x and μ y They are represented by the following formulas (4) and (5), Entropy = -∑ i ∑ j P(i, j)log(P(i, j)) (1) Cluster shadow = ∑ i ∑ j (i+j-μ x -μ y ) 3 P(i,j) (3) μ x ∑ i ∑ j i(P(i,j)) (4) μ y ∑ i ∑ j j(P(i,j)) (5)。 2. The hot rolled steel sheet according to claim 1, characterized in that: The average crystal grain size in the surface layer region, which is a region starting from the surface and ending at a position at a depth of 20 μm in the plate thickness direction, is less than 3.0 μm.
3. The hot rolled steel sheet according to claim 1 or 2, characterized in that: The chemical composition contains, by mass%, one or more elements selected from the following: Ti: 0.001~0.500%, Nb: 0.001~0.500%, V:0.001~0.500%、 Cu: 0.01-2.00%, Mo: 0.01~1.00%, Ni: 0.02-2.00%, B:0.0001~0.0100%、 Ca: 0.0005~0.0200%, Mg: 0.0005~0.0200%, REM: 0.0005~0.1000%、 Bi: 0.0005~0.0200%, As: 0.001~0.100%, Zr:0.01~1.00%、 Co: 0.01~1.00%, Zn: 0.01~1.00%, W: 0.01~1.00%, and Sn: 0.01~0.05%.
Citation Information
Patent Citations
1*22di alkoxycarbonylmethylamino ethylenee1*22disulfonic acid phenyl ester derivative* its preparation* and herbicide containing said compound
JP1981055394A
Model generation device, model generation method, and model generation program
JP2022142994A
Hot-rolled steel sheet and production method therefor, cold-rolled steel sheet and production method therefor, production method for cold-rolled annealed steel sheet, and production method for hot-dip galvanized steel sheet
WO2020044445A1